2018
DOI: 10.1002/star.201800093
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Chemically‐Modified Cassava Starch Grafted with Poly(2‐Ethylhexyl Acrylate) for Blending with Poly(Lactic Acid)

Abstract: Native cassava starch (CS) is chemically modified by grafting with 2-ethylhexyl acrylate (EHA) monomer to make it more hydrophobic for improved blending with poly(lactic acid) (PLA). Grafting is carried out using CS:EHA weight ratios of 2:1, 1:1, 1:2, and 1:3 in a methanol-water solvent mixture at 45 C for 48 h. L-Ascorbic acid and hydrogen peroxide are used as the redox initiating system. Following purification, the poly(2-ethylhexyl acrylate)-grafted starch, starch-g-PEHA, is obtained either as a finely divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Figure 1(d) shows the typical wave pattern when brittle fracture occurred. This can confirm the brittleness of PLA as a morphological characteristic (Martínez-Vázquez et al 2014;Bunkerd et al 2018). Figure 2 shows the 3D-printed PLA composite in which only 5 phr of MA-EPDM was added to PLA.…”
Section: Morphological Propertiesmentioning
confidence: 56%
“…Figure 1(d) shows the typical wave pattern when brittle fracture occurred. This can confirm the brittleness of PLA as a morphological characteristic (Martínez-Vázquez et al 2014;Bunkerd et al 2018). Figure 2 shows the 3D-printed PLA composite in which only 5 phr of MA-EPDM was added to PLA.…”
Section: Morphological Propertiesmentioning
confidence: 56%
“…Morphological characteristics at the tensile fractured surfaces of samples were observed by SEM; the images are shown in Figure 6. Both the PLA and the extruded PLA exhibited smooth fractured surfaces (Figure 6a,b), indicating their rigidity and brittleness 46 . By blending with different variations of PBAT/NR blend, the obtained PLA/PBAT/NR ternary blends showed rougher surfaces with stretched fibrils, which might relate to one or more elastic components, that is, PBAT and/or NR, as clearly seen in Figure 6c,d.…”
Section: Resultsmentioning
confidence: 90%
“…The higher tensile strength and Young's modulus of PLA/-PBAT/NR ternary blends were explained by the presence of the strong and stiff PLA. 46 By blending with different variations of PBAT/NR blend, the obtained PLA/PBAT/NR ternary blends showed rougher surfaces with stretched fibrils, which might relate to one or more elastic components, that is, PBAT and/or NR, as clearly seen in Figure 6c,d. Previous articles also reported that PBAT formed fibrils in the matrix of PLA/PBAT blends.…”
Section: Mechanical Propertiesmentioning
confidence: 88%
“…According to standard D7334, when the contact angle is higher than 90º, the silanized starches are hydrophobic and the wetting of these polysaccharides is reduced (Bergel et al, 2020). Bunkerd et al (2018) obtained cassava starch modified with 2-ethylhexyl acrylate, and it presented a contact angle higher than 80º. This allowed the researchers to adhere the starch to the hydrophobic PLA matrix.…”
Section: Contact Anglementioning
confidence: 99%